A diagnostic pitfall in suspected giant cell arteritis: metastatic renal cell carcinoma mimicking the temporal artery halo sign on ultrasound - Yamancan, Gulsah; Karatas, Ahmet (Springer Heidelberg, 2026)
[Abstract Not Available]
Keywords: Giant Cell Arteritis; Temporal Arteries; Ultrasonography; Renal Cell Carcinoma; Differential Diagnosis